AB0773 PSORIATIC ARTHRITIS IMPACT OF DISEASE QUESTIONNAIRE SCORES ARE CORRELATED WITH DISEASE ACTIVITY, AS MEASURED BY CDAPSA, IN PATIENTS WITH PSORIATIC ARTHRITIS. (June 2019) - Orbai, Ana-Maria; Krueger, Klaus; Behrens, Frank; Kiltz, Uta; Guerette, Benoit; Mellars, Lillian; Brunori, Michele; Wollenhaupt, Jurgen
Abstract : Background: LAPIS-PsA is an ongoing, national, 52-week, multicenter, prospective, non-interventional study assessing long-term treatment with apremilast (APR) in adult patients with active psoriatic arthritis (PsA) in routine clinical practice in Germany. Objectives: The current interim analysis assesses the clinical effectiveness of aPR, as measured with the Clinical Disease activity index for PsA (cDAPSA) and its core components, as well as PsA health-related quality of life (HRQoL), measured with the 9-domain PsA Impact of Disease Questionnaire (PsAID9). In addition, correlations between cDAPSA and PsAID9 were assessed. Methods: The interim analysis included data obtained at baseline (BL), Visit 1 (V1; ≥1 month), Visit 2 (V2; ≥4 months) and Visit 3 (V3; ≥7 months); all available data for patients treated with aPR 30 mg twice daily were included in the analysis. A subgroup analysis was performed among patients categorized by cDAPSA disease activity scores at BL. Clinical characteristics and disease assessments at BL and V1-3 were assessed. Mean PsAID9 scores and proportions of patients meeting the PsAID Patient-Acceptable Symptom State (PASS), defined as a PsAID9 score of 4, were assessed by cDAPSA category at BL. Analyses are based on data as observed at each visit. Pearson's correlations were calculated between cDAPSA and PsAID9 at BL, V1, V2 and V3. Results: A total of 394 patients were included in the analysis population (mean age: 55.1 years; female: 55.1%; previous biologic use: 25.4%). At BL, patients had a mean PsAID9 score of 5.3 and a mean cDAPSA score of 26.6. Continuous improvements in swollen/tender joint counts and patient-reported pain and disease activity were observed with continued aPR treatment (Table). Patients reported incrementally reduced mean cDAPSA scores and consistent improvements in PsAID9 scores from BL to V3. Patients with low disease activity (cDAPSA >4 to ≤13) at BL had a mean (SD) PsAID9 score of 3.4 (1.7) with 71.1% in PsAID PASS (Figure). Those with moderate (cDAPSA >13 to ≤27) and high (cDAPSA >27) disease activity had mean (SD) PsAID9 scores of 5.3 (1.9) and 6.1 (1.8), with 26.6% and 11% showing PsAID PASS, respectively. At follow-up visits, greater proportions of patients achieving cDAPSA low disease activity or remission also achieved PsAID PASS (Figure). Significant moderate to high correlations were observed between cDAPSA and PsAID9 at BL (Pearson's coefficient r =0.43), V1 ( r =0.51; P <0.0001), V2 ( r =0.64; P <0.0001) and V3 ( r =0.64; P <0.0001). Conclusion: Results from this observational PsA study of aPR demonstrate a significant correlation between disease activity, as assessed by cDAPSA, and PsA-specific life impact/HRQoL, as measured by PsAID9. More patients met the PsAID PASS cutoff while achieving remission or lower disease activity, and improvements in PsA disease activity are associated with the PsAID PASS from a life impact perspective. Disclosure of interests: Ana-Maria Orbai Grant/research support from: abbVie, Celgene, Horizon Pharma, Janssen, Lilly, and Novartis, Consultant for: Lilly, Janssen, Novartis, Pfizer, and UCB, Klaus Krueger: None declared, Frank Behrens Grant/research support from: abbVie, Pfizer, Roche, Chugai, Prophylix, Bioline, Novartis, Consultant for: abbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Speakers bureau: ad board: abbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Uta Kiltz Grant/research support from: abbVie, Chugai, Eli Lilly, Grünenthal, Janssen, MSD, Novartis, Pfizer, Roche, and UCB., Consultant for: abbVie, Chugai, Eli Lilly, Grünenthal, Janssen, MSD, Novartis, Pfizer, Roche, and UCB., Benoit Guerette Employee of: Celgene Corporation, Lillian Mellars Employee of: Celgene Corporation, Michele Brunori Employee of: Celgene Corporation, Jurgen Wollenhaupt Grant/research support from: Pfizer inc, Consultant for: Pfizer inc, Speakers bureau: Pfizer inc